(3JHUjQ GdefJHg HJMQjQ GdeTJHgs - (3CMeO Hf Ydj Hf eMeO GdcfGfj GdYSbdGfj, CHh GdaVd, TgGH GdOjf, GHf nMnLQ,J (B852 (3g` s
(3ChdgG (B:s
(3GdMeO ddg LGeY GdfGS djhe dGQjH ajg CeG HYO aEfi deG YdbJ cJGH GdeTJHg GdPi dNUg GdMGaX GdTgjO CHh YHO Gddg GdPgHi s
(3BNQgG (B:s
(3hdG jSJZfi WGdH GdMOjK Yf VHW eG jQO ai Pdc ef GdCSeGA hdhde jcf dg QhGjI hGddg Gdehab ddUhGH s
(3HgG fXGe GdJYbjHIs
(3aQZ ef JCdjag SfI (B816s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B173s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdeYGQa GdYGeIs